SIFAT ANTIKAPANG EKSTRAK ZAT WARNA BUNGA KNOP (Gomphrena globosa L) - Miksusanti, ; Setiawaty Yusuf, (Matematika dan Sains, 2011)
The aims of research was to study the color subtance of knop flower as antifungi. It was extracted by maceration using ethanol solvent. Antifungi assay against Aspergillus flavus and Aspergillus niger was conducted using contact method. Results of research showed that adding of color substance of knop flower extract of 30% decreased cell mass of A. flavus of 47.22% and A. niger of 25%. The MIC value were 45% for A. Flavus and 48% for A. niger.